Role of Transamin in Reduction of Seroma in Post-Operative Mastectomy - Omer Farooq, Hafiz Ali Muhammad, Arshia Rasool, Qazi Muhammad Sibghatullah, Aleena Hameed, Khaula Asif (Pakistan Journal of Medical & Health Sciences, 2022)
Objective:The purpose of this study to determine the effectiveness of transamin in reduction of seroma in post-operative mastectomy. Study Design:Retrospective study Place and Duration: District Headquarter Hospital Attock and Medicare Hospital, Attock. September 2021-July 2022. Methods: There were 40 females had breast cancer with age 20-65 years were included. Patients were underwent for mastectomy and admitted to hospital. After obtaining informed written consent detailed demographics of enrolled cases included age, body mass index and socio-economic status was recorded. After surgery patients received injection of tranexamic acid. Outcomes among all patients were assessed in terms of reduction in seroma formation, wound infection, amount of drainage and time of drainage. SPSS 22.0 was used to analyze all data. Results: We found that 7 (20%) patients had age 21-30 years, 12 (30%) cases had age 31-40 years, 17 (42.5%) cases had age 41-50 years and 4 (10%) cases had age 51-65 years. 26 (65%) patients had BMI >25kg/m2 and 14 (35%) had BMI <25kg/m2. There were 22 (55%) patients had poor socio-economic status. Mean amount of drainage was 812.7±99.24 ml and mean time of drainage was 7.5±12.40 days. Frequency of seroma formation was found in 5 (12.5%) cases in which mostly had BMI >25kg/m2 and had increased age. Wound infection found in 3 (7.5%) cases. Conclusion:We concluded in this study use of tranexamic acid among patients undergoing mastectomy was affective and useful in terms of reduction in seroma formation and lower number of wound infection. Except this duration and volume of drainage was also seen lower in our study. Keywords: Breast Cancer, Mastectomy, Seroma, Tranexamic Acid, Complications